PENGEMBANGAN MODEL PEMBELAJARAN SOFT SKILLS DAN HARD SKILLS UNTUK SISWA SMK - Widarto, Widarto; Pardjono, Pardjono; Widodo, Noto (Jurnal Cakrawala Pendidikan, 2012)
Abstrak: Pengembangan Model Pembelajaran Soft Skills dan Hard Skills untuk Siswa SMK. Era global menuntut sumber daya manusia yang memiliki daya saing, adaptif dan antisipatif, mampu belajar, terampil, mudah beradaptasi dengan teknologi baru. Profil tenaga kerja yang dibutuhkan pasar adalah yang kuat pada aspek soft skills dan hard skills. Ada tiga alternatif model pendidikan yang memadukan hard skills dan soft skills, yaitu (1) aspek soft skills dan hard skills dilaksanakan di sekolah; (2) aspek soft skills dilaksanakan di sekolah, sedang hard skills dilaksanakan bersamaan praktik kerja di DUDI; atau (3) aspek soft skills dilaksanakan di sekolah, sedang aspek hard skills ketika praktik kerja di teaching factory. Untuk itu, struktur kurikulum SMK disusun sesederhana mungkin dengan tetap mengacu Kurikulum Nasional yang digunakan dengan tekanan pada aspek soft skills dan mengintegrasikannya ke dalam silabus dan RPP. Karakteristik guru yang diperlukan adalah: (1) the adaptor; (2) the visionary; (3) the collaborator; (4) the risk taker; (5) the leaner; (6) the communicator; (7) the model; dan (8) the leader. Selain itu, diperlukan dukungan stake holders yakni dinas pendidikan setempat, masyarakat dan DUDI. Kata Kunci: model pembelajaran, pendidikan soft skills, hard skills, siswa SMK, tenaga kerja Abstract: Development of Soft Skills and Hard Skills Learning Model for Students of SMK. The global era demands human resources that are competitive, adaptive and anticipatory, able to learn, skillful, adaptable to new technology. Labors’ profile that market needs are someone who has a strong skill in the aspect of soft skills and hard skills. There are three alternative education modela that combines hard skills and soft skills, namely (1) aspects of soft skills and hard skills present in the school; (2) aspects of soft skills is implemented in schools, while the hard skills is being held during working practices in DUDI; (3) soft skills aspect is implemented in schools, while aspects of hard skills when working practices in teaching factory. For that, the structure of vocational curriculum is arranged as simple as possible referring to the National Curriculum which is used with an emphasis on aspects of soft skills and is integrated into the syllabus and lesson plans. Teachers’characteristics requires: (1) the adaptor; (2) the visionary; (3) the collaborators; (4) the risk taker; (5) the leaner; (6) the communicator; (7) the model; and (8) the leader. In addition, it requires the support of local education stakeholders, communities and DUDI.